1995
DOI: 10.1002/hlca.19950780118
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Rate Constants for the Addition of Cyanomethyl (·CH2CN) and (tert‐Butoxy)carbonylmethyl (·CH2CO2C(CH3)3) radicals to alkenes in solution

Abstract: Absolute rate constants and their temperature dependence were determined by time-resolved electron spin resonance for the addition of the radicals 'CH,CN and .CH,CO,C(CH,), to a variety of mono-and 1,l-disubstituted and to selected 1,2-and trisubstituted alkenes in acetonitrile solution. To alkenes CH,=CXY, .CH,CN adds at the unsubstituted C-atom with rate constants ranging from 3.3.10' M-Is- ' (ethene) to 2.4.106 M-IS-'( 1 , ldiphcnylethene) at 278 K, and the frequency factors are in the narrow range of log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 48 publications
6
30
1
Order By: Relevance
“…On the other hand, experimental studies led to the conclusion that the methyl radical is nucleophilic, whereas the cyanomethyl radical 18 and the tert -butoxycarbonylmethyl radical 19 are ambiphilic (borderline cases). Later, however, Fischer et al suggested that the latter two radicals are weakly electrophilic …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, experimental studies led to the conclusion that the methyl radical is nucleophilic, whereas the cyanomethyl radical 18 and the tert -butoxycarbonylmethyl radical 19 are ambiphilic (borderline cases). Later, however, Fischer et al suggested that the latter two radicals are weakly electrophilic …”
Section: Introductionmentioning
confidence: 99%
“…The addition of carbon-centered radicals to olefins is one of the most used reactions for the construction of C–C bonds. , Despite its apparent simplicity, this process is mechanistically intriguing as it relies on a complex interplay between enthalpic, steric, and polar effects. State correlation diagrams that describe these transformations involve three components: the reactants in (i) the ground, (ii) the excited state, and (iii) the polar charge transfer configuration (CTC). , As a result, the identification of polarity-matched systems might result in more facile reactions owing to the stabilization of the CTC in the transition state . A classical example is the addition of electrophilic radicals (e.g., malonyl radical) to electron-rich olefins like enol ethers and enamines (Scheme A). , …”
mentioning
confidence: 99%
“…The m / z pattern is perfectly consistent with a significant concentration of CH 2 CN • (Figure S3 and Supporting Information D for details). It is well-known that CH 2 CN • can be generated directly from CH 3 CN by homolytic cleavage of a C–H bond. Moreover, the cyanomethyl radical (CH 2 CN • ) is known to react with C–C double bonds and arenes forming C–C bonds.…”
mentioning
confidence: 99%